ANALISIS HUKUM EKONOMI ISLAM PADA PRAKTIK BISNIS MLM SYARIAH PT. K-LINK INDONESIA: (Studi Kasus Diamond Manager di Desa Barurejo Kecamatan Siliragung Kabupaten Banyuwangi) - Muh. Ainun Najib (Jurnal Ekonomi Syariah Darussalam, 2025)
This study aims to determine the practices of PT. K-Link Indonesia's sharia-compliant multi-level marketing business and to examine the legal perspective of Islamic economics on PT. K-Link Indonesia's sharia-compliant MLM business practices among diamond managers in Barurejo Village, Siliragung District, Banyuwangi Regency. The research findings indicate that PT. K-Link Indonesia utilizes a sharia-compliant multi-level marketing system. The 2019 Nahdlatul Ulama National Conference (MUNAS NU) in Commission A (Bahtsul Masail Waqi'iyah) ruled that money games are haram (forbidden). The study concludes that PT. K-Link Indonesia's multi-level marketing business is permissible because it falls under the category of muamalah (social transactions), whose basic law is permissible unless there is evidence to prohibit it. However, if elements found within the MLM business system contain elements prohibited by Islam, then the business is prohibited, and this is referred to as Sharia-compliant Multi-Level Marketing (PLBS).